Qualitative autoradiography with polycarbonate foils enables histological and track analyses on the same section - Portu, Agustina Mariana (2013)
Neutron autoradiography is an imaging methodology that enables analysis of the spatial distribution of heavy ion emitters in a given material. In particular, it allows localization of 10 B in a tissue section put in contact with a nuclear track detector. Boron imaging is essential when considering boron neutron capture therapy as an option for treating cancerous tumors. A description of the autoradiography method is presented together with specific characteristics and technical details developed in our laboratory. We propose a new mounting technique to compare autoradiography images with the same section that gave rise to the latent tracks. The solid state nuclear track detector is polycarbonate, because it can be processed rapidly to obtain the autoradiographic results. It is a transparent material, which allows visualization of the sections mounted on it. Tissue can be removed easily and background is minimal.